Combined Endodontic and Surgical Therapy for Resolution of Type III Dens Invaginatus - Fonseca, Francielen Oliveira; Vasconcellos, BetÃ¢nia Canal; Costa, Marcela Martins; Ribeiro Sobrinho, AntÃ´nio Paulino; Tavares, Warley Luciano Fonseca (Iranian Endodontic Journal, 2020)
Dens invaginatus is an abnormal dental developmental, probably resulting of the invagination of mineralized tissues from the tooth crown surface before its calcification. The teeth that are most affected by this abnormality are the maxillary lateral incisors. This dental developmental anomaly has various types and the rarest is type III which has the worst prognosis, because of its complex anatomy. Conventional root canal therapy may not sufficiently resolve the case itself and in some circumstances the surgical intervention is also necessary. This report addresses a complex combined endodontic treatment of a type III dens invaginatus in a maxillary lateral incisor in an 18 years-old female patient, with an extensive periapical lesion affecting the buccal and palatine cortical bone, diagnosed by cone-beam computed tomography (CBCT). The case was conducted with the combination of endodontic and surgical treatment, under the use of the surgical operating microscope. The association of CBCT, visual magnification, XP-endo Finisher, bioceramic sealer, MTA Repair HP and bone graft were important to ensure predictable success. Keywords: Bioceramic Sealer; Dens Invaginatus; Endodontic Surgery; Endodontic Therapy; Periapical Lesion